Heterogeneity of the horizontal environment drives community assemblages and species coexistence of prokaryotic communities in cold seep sediments - Wu, Qixuan; Feng, Jingchun; Huang, Yongji; Zhong, Song; Li, Cun; Zhang, Si (Frontiers in Microbiology, 2025)
IntroductionMicroorganisms play important roles in methane oxidation and carbon turnover of cold seep ecosystem. Although the microbial diversity of cold seep sediments has been reported, the community assembly processes, species coexistence patterns, and their underlying drivers across horizontal gradients of distinct cold seep habitats remain largely unexplored. To address this gap, we conducted a comprehensive investigation of prokaryotic communities in various habitats of the Haima cold seeps, aiming to elucidate the mechanisms governing microbial community construction in this sedimentary environment.MethodsSediment samples were collected from the Haima cold seep and subsequently analyzed through an integration of geochemical measurements and 16S rRNA gene sequencing.ResultsThe prokaryotic community at the methane seep site exhibited lower α-diversity than those at other sites. Halobacterota dominated the methane seep site, whereas higher abundances of Chloroflexi and Asgardarchaeota were observed in the faunal sites. The assembly process of the bacterial community in the methane seep site was primarily governed by stochastic processes, while the archaeal community was mainly formed by deterministic processes. In faunal sites, both stochastic and deterministic processes influenced prokaryotic community assembly. Heterogeneity of the horizontal environment such as the content of CH4, Ba2+, total inorganic carbon, and SO42− significantly influenced prokaryotic community diversity and governed the community assembly. Additionally, co-occurrence network analysis revealed higher connectivity and more complex species interactions in the bacterial network at the methane seep site compared to other sites; the opposite trend was observed for archaea.DiscussionThis study demonstrated that environmental heterogeneity is a key determinant of prokaryotic community diversity and composition in the cold seep, driving distinct community assembly and species coexistence patterns across different habitats.